2019
DOI: 10.1017/fms.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Regularization of Non-Normal Matrices by Gaussian Noise—the Banded Toeplitz and Twisted Toeplitz Cases

Abstract: We consider the spectrum of additive, polynomially vanishing random perturbations of deterministic matrices, as follows. Let M N be a deterministic N × N matrix, and let G N be a complex Ginibre matrix. We consider the matrix M N = M N + N −γ G N , where γ > 1/2. With L N the empirical measure of eigenvalues of M N , we provide a general deterministic equivalence theorem that ties L N to the singular values of z − M N , with z ∈ C. We then compute the limit of L N when M N is an upper triangular Toeplitz matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…The choice of γ in each of the three cases given in Corollary 1.8 is so that (1.11) is satisfied. Theorem 1.7 and its corollary are similar to several recent works concerning fixed matrices perturbed by random matrices [7,8,10,29,60,61,62,73]. The case when E contains independent Gaussian entires was investigated in [7,29,60,61,62].…”
Section: 14)supporting
confidence: 60%
See 1 more Smart Citation
“…The choice of γ in each of the three cases given in Corollary 1.8 is so that (1.11) is satisfied. Theorem 1.7 and its corollary are similar to several recent works concerning fixed matrices perturbed by random matrices [7,8,10,29,60,61,62,73]. The case when E contains independent Gaussian entires was investigated in [7,29,60,61,62].…”
Section: 14)supporting
confidence: 60%
“…Theorems 1.4 and 1.5 are closely related to a number of techniques used in the random matrix theory literature to study non-Hermitian matrices, including those found in [5,7,24,65]. The authors are not aware of any works where these results are stated in the deterministic forms given above.…”
Section: Introductionmentioning
confidence: 96%
“…evaluating logarithmic potentials amounts to computing determinants. In their study of the spectrum of small, noisy perturbations of non-normal matrices, the authors of [1] have identified a certain deterministic equivalent result, which we now present.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 71%
“…The proof in [1] uses in an essential way the unitary invariance of G N , and probabilistic arguments. However, it does not directly extend to other noise models, not even to the case where G N is a matrix consisting of independent real standard Gaussian variables.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…In the noncentered case, Davies and Hager [15] showed that if A is a Jordan block and h n for some appropriate , then almost all of the eigenvalues of A g G n lie near a circle of radius 1=n with probability 1 o n .1/. Basak, Paquette, and Zeitouni [4,5] showed that for a sequence of banded Toeplitz matrices A n with a finite symbol, the spectral measures of A n gn G n converge weakly in probability, as n 3 I, to a predictable density determined by the symbol. Both of the above results were recently and substantially improved by Sjöstrand and Vogel [37,38], who proved that for any Toeplitz A, almost all of the eigenvalues of A g n G n are close to the symbol curve of A with exponentially good probability in n. Note that none of the results mentioned in this paragraph explicitly discuss the .…”
Section: Related Workmentioning
confidence: 99%